Pelatihan Kardiovaskular untuk Kalangan Non-Medis dengan Media Daring di Era Pandemi Covid-19 - Sidhi Laksono Purwowiyoto; Steven Philip Surya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Health literacy is one of the essential components of the health sector. Health literacy could diminish mortality and morbidity, especially in cardiovascular disease. Until now, coronary artery disease is one of the most threatening diseases in our society. Pandemic forces our world to change into a digital era, including in health education. Surprisingly, online education is increasing health literacy as effectively as the conventional method. This study aims to determine the effect of a training program on knowledge of non-medical society about heart and blood vessel disease. This research was comparing pre-test and post-test scores for non-medical societies in webinars about coronary artery disease. From our result, we found that online education could increase the scope of the participant (48% of participants come from outside Jakarta). Our participants also quite vary from youngsters to senior citizens, from 18 to 69 years old. The online webinar could increase health literacy in coronary artery disease significantly (pre-test score: 50 (10-100), post-test score: 60 (20-100), p-value <0.001). Webinars about coronary artery disease could increase health literacy in non-medical society and it seems to be an effective method during pandemic COVID-19.